Pengelolaan Lingkungan Belajar sebagai Strategi Penciptaan Iklim Kelas yang Kondusif - Silfi Putri Suciyati; Itna Khusnatul Azizah; Dwi Nur Lailiya Rahmadani; Lailatul Usriyah (Advances In Education Journal, 2026)
The management of the learning environment is one of the key strategies in classroom management for creating a conducive classroom climate. The learning environment encompasses not only the physical aspects of the classroom but also the social, emotional, and psychological aspects that influence students’ interactions and engagement in the learning process. This article aims to conceptually examine the role of learning environment management as a strategy for creating a conducive classroom climate based on a literature review of various reputable journals. The method used is a literature review analyzing relevant scientific articles published in the last five years. The results of the study indicate that learning environment management, when implemented in a planned and integrated manner—encompassing physical, social, and emotional aspects—contributes to the creation of a classroom climate that is safe, comfortable, and supportive of students’ active engagement. Thus, learning environment management can serve as a classroom management strategy to support effective and sustainable learning processes.